Transferrin-Modified Nanoparticles for Photodynamic Therapy Enhance the Antitumor Efficacy of Hypocrellin A - Xi Lin; Shu-Zhen Yan; Shan-Shan Qi; Qiao Xu; Shuang-Shuang Han; Ling-Yuan Guo; Ning Zhao; Shuang-Lin Chen; Shu-Qin Yu (Frontiers Media S.A., 2017)
Photodynamic therapy (PDT) has emerged as a potent novel therapeutic modality that induces cell death through light-induced activation of photosensitizer. But some photosensitizers have characteristics of poor water-solubility and non-specific tissue distribution. These characteristics become main obstacles of PDT. In this paper, we synthesized a targeting drug delivery system (TDDS) to improve the water-solubility of photosensitizer and enhance the ability of targeted TFR positive tumor cells. TDDS is a transferrin-modified Poly(D,L-Lactide-co-glycolide (PLGA) and carboxymethyl chitosan (CMC) nanoparticle loaded with a photosensitizer hypocrellin A (HA), named TF-HA-CMC-PLGA NPs. Morphology, size distribution, Fourier transform infrared (FT-IR) spectra, encapsulation efficiency, and loading capacity of TF-HA-CMC-PLGA NPs were characterized. In vitro TF-HA-CMC-PLGA NPs presented weak dark cytotoxicity and significant photo-cytotoxicity with strong reactive oxygen species (ROS) generation and apoptotic cancer cell death. In vivo photodynamic antitumor efficacy of TF-HA-CMC-PLGA NPs was investigated with an A549 (TFR positive) tumor-bearing model in male athymic nude mice. TF-HA-CMC-PLGA NPs caused tumor delay with a remarkable tumor inhibition rate of 63% for 15 days. Extensive cell apoptosis in tumor tissue and slight side effects in normal organs were observed. The results indicated that TDDS has great potential to enhance PDT therapeutic efficacy.